Evaluation Of Virtual Bolus For Tomotherapy Dose Optimization In Superficial Cancers - Ooi, Gim Chee (2020)
This study evaluates the radiation dosimetry effects of using virtual-bolus (VB) in TomoTherapy Treatment Planning System (TPS) for Planning-Target-Volume (PTV) that extends to skin or body-surface. PTV was contoured on phantom that extended to the phantom surface. Virtual bolus of various thickness (0.2 cm / 0.4 cm / 0.6 cm) and densities (0.5 g/cm3 or 1.0 g/cm3) combinations were drawn to provide “virtual” build-up region for the TPS and then optimized with TomoTherapy TPS. EBT3 Gafchromic Film was calibrated and used to analyze the dose profiles across PTV and the phantom surface, and gamma analysis was peformed for the photon fluence with Distance-to-Agreement (DTA) 3 mm and Dose Difference 3% criteria. TomoTherapy Planned-Adaptive software was used to analyze the delivered Dose-Volume-Histograms (DVHs) reconstructed from the mega-voltage computed tomography (MVCT) acquisition. Without VB used, the control set optimization showed maximum dose close to 110% at the phantom edge or the surface due to lack of build-up region. VB of 0.2 cm was shown to be unable to provide adequate build-up area. The use of VBs of 0.4 cm and 0.6 cm for dose optimization were able to control the maximum dose in the TPS and also in the actual radiation delivery. However, VB of 0.6 cm exhibited large reduction in dose coverage (95%) in the actual radiation delivery.